The development of assertive behavior and creative thinking of early childhood students by STEM Education - โลหา, พัทฐรินทร์; จงกลกลาง, สิรินาถ (Ratchaphruek Journal, 2019)
The purposes of STEM Education from this quasi experimental research were to compare the assertive behavior and creative thinking of kindergarten 2 before and after using STEM Education. The cluster random sample group of this research was 30 students of K 2/2 in the second semester of 2017academic year at The Demonstration School of Nakhon Ratchasima Rajabhat University. The research instrumentswere1) STEM education’ s experience lesson plan, 2) Assertive behavior’s observation forms, and 3) Creative thinking measurement form. The collected data were analyzed by frequency, percentage, mean, standard deviation and t-test for dependent statistic. The results of the research were as follow; (1) before learning, mean of assertive behavior was 48.47, at 80.77%.The after learning, mean was 59.03, at 98.38%, mean of progress was 10.57.The after learning was higher than before learning at a significance level of .05, (2) before learning, mean of creativity was 35.57, at 49.39%. The after learning, mean was 49.73, at 69.06%, mean of progress was 14.17. The after learning was higher than before learning at a significance level of .05.